The Effect of Workload and Work Environment on Employee Performance and Work Stress as Intervening Variable - Gheazella Ramadhianti Ridwan; Sandra Irawati; Ardik Praharjo (Universitas Muhammadiyah Malang, 2022)
The purpose of this study was to determine the effect of workload and work environment on employee performance mediated by work stress. The type of research used is a survey research method. Data collection was done by using a questionnaire. For the number of questionnaires distributed to employees at BPBD Malang City. Testing the instrument in this study uses validity and reliability tests in which the results of the questionnaire can be said to be valid and reliable. The results of the classical assumption test in this study are Normal distribution and there are no symptoms of multicollinearity and heteroscedasticity. The data analysis technique used is path analysis and also the Sobel test. The results of this study indicate that workload and work environment affect employee performance through work stress.